Potent and Broad-Spectrum Antimicrobial Activity of Analogs from the Scorpion Peptide Stigmurin - Bruno, Amorim-Carmo, (2021)
Scorpion venom constitutes a rich source of biologically active compounds with high potential for therapeutic and biotechnological applications that can be used as prototypes for the design of new drugs. The aim of this study was to characterize the structural conformation, evaluate the antimicrobial activity, and gain insight into the possible action mechanism underlying it, for two new analog peptides of the scorpion peptide Stigmurin, named StigA25 and StigA31. The amino acid substitutions in the native sequence for lysine residues resulted in peptides with higher positive net charge and hydrophobicity, with an increase in the theoretical helical content. StigA25 and StigA31 showed the capacity to modify their structural conformation according to the environment, and were stable to pH and temperature variation-results similar to the native peptide. Both analog peptides demonstrated broad-spectrum antimicrobial activity in vitro, showing an effect superior to that of the native peptide, being non-hemolytic at the biologically active concentrations. Therefore, this study demonstrates the therapeutic potential of the analog peptides from Stigmurin and the promising approach of rational drug design based on scorpion venom peptide to obtain new anti-infective agents.